OUTLOOK OF ARBITRARY MEASURES OF FAIR AND EQUITABLE TREATMENT UNDER HEALTH URGENCY: THE WAIVER OF PHARMACEUTICAL PATENT - Musu, Clara Amanda; Napitupulu, Dona Regina; Qurratu’aini, Marla Satika (Department of Transnational Business Law, Faculty of Law Universitas Padjadjaran, 2021)
Patent has long been recognized as an important subject of investment particularly for Pharmaceutical Companies. In its development, patents have become one of the most prominent tools in international health investment for its economic benefit sourced from its exclusive right. Most of the Multilateral and Bilateral Investment Treaties recognized intellectual property rights as protected investments, which allows patent holders to benefit from the substantive and procedural safeguards granted by the applicable treaty for foreign investments. In the situation of health urgency, many patents rights are being waived by the government to make the innovation more affordable and accessible to citizens. In this situation, tension in the governance of pharmaceutical patents between patent holders and state authorities is an example of a broader recurring dynamic in international law: the tension between foreign investors' private interests and the host state's regulatory autonom. This research paper will discuss whether the patent waiver enacted by the government is considered as an arbitrary action under the Fair and Equitable Treatment standard as it causes harm to the foreign investor by analyzing several precedent jurisprudences through juridical normative methods